2011
DOI: 10.1371/journal.pone.0026369
|View full text |Cite
|
Sign up to set email alerts
|

Strain-Dependent Host Transcriptional Responses to Toxoplasma Infection Are Largely Conserved in Mammalian and Avian Hosts

Abstract: Toxoplasma gondii has a remarkable ability to infect an enormous variety of mammalian and avian species. Given this, it is surprising that three strains (Types I/II/III) account for the majority of isolates from Europe/North America. The selective pressures that have driven the emergence of these particular strains, however, remain enigmatic. We hypothesized that strain selection might be partially driven by adaptation of strains for mammalian versus avian hosts. To test this, we examine in vitro, strain-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 52 publications
0
17
1
Order By: Relevance
“…This possibility has been tested by comparing the different efficiencies with which ROP16s of different strains activate their STAT targets in mammals (mice and humans) vs. birds (chickens). The results showed that, contrary to the model, the strain-specific differences in ROP16's effect were independent of host species, at least in vitro [10]! This led to a friendly amendment to the model—i.e., that the differences between the hosts that the strains have evolved to infect might be in the environment experienced by that host rather than the species of host, per se.…”
Section: How Were the Rop Kinases/pseudokinases Discovered And Whacontrasting
confidence: 59%
See 1 more Smart Citation
“…This possibility has been tested by comparing the different efficiencies with which ROP16s of different strains activate their STAT targets in mammals (mice and humans) vs. birds (chickens). The results showed that, contrary to the model, the strain-specific differences in ROP16's effect were independent of host species, at least in vitro [10]! This led to a friendly amendment to the model—i.e., that the differences between the hosts that the strains have evolved to infect might be in the environment experienced by that host rather than the species of host, per se.…”
Section: How Were the Rop Kinases/pseudokinases Discovered And Whacontrasting
confidence: 59%
“…The best-studied active kinases are ROP16 and ROP18. ROP16 is a tyrosine kinase that mimics the action of host JAKs by phosphorylating the key tyrosine needed for activation of STATs [10][13]. This is an extremely rapid process such that within one minute of the commencement of invasion, STAT3 and STAT6 (at least) are activated and translocated to the nucleus where they turn on many immune response genes and downregulate the expression of others.…”
Section: What Comprises the Rop Cargo And What Do The Rops Do?mentioning
confidence: 99%
“…These include chromosome VIIb (1,022 mouse genes), on which ROP16, the tyrosine kinase that activates STAT3 and STAT6, is located (10-12), and chromosome X (261 mouse genes), on which the NF-B regulator GRA15 is located (13). As was found in previous QTL mapping analyses of human and chicken fibroblasts infected with the same Toxoplasma progeny (11,26), the host genes with the highest logarithm of odds (LOD) scores, measuring the strength of the association between a Toxoplasma marker and host cell gene expression, mapped to chromosome VIIb (maximum LOD score ϭ 15.22). Gene Set Enrichment Analysis (GSEA) (27) and distal regulatory element enrichment (DiRE) analysis (http://dire.dcode.org/) of the mouse genes that mapped to Toxoplasma chromosome VIIb indicated that their transcription was largely controlled by transcription factors STAT3, STAT5, and STAT6, which are targets of ROP16.…”
Section: Qtl Mapping Reveals a Region On Toxoplasma Chromosome IX Thamentioning
confidence: 89%
“…Hammondia hammondi ROP16 and GRA15 are also functional effectors. Specifically, expressing H. hammondi ROP16 in type II T. gondii significantly increased STAT6 phosphorylation and translocation to the nucleus , which is similar to the type I and III T. gondii ROP16 alleles . Importantly, the STAT6 induction was significantly higher than type II T. gondii expressing an additional copy of a type II ROP16 allele, providing strong evidence that the ‘active’ allele of ROP16 with respect to STAT6 activation is ancestral to the T. gondii / H. hammondi split.…”
Section: Conservation Of Known T Gondii Secreted Effectors In H Hammentioning
confidence: 67%